Analisis Faktor-Faktor Yang Memengaruhi Potensi Penerimaan Pajak Parkir Di Kabupaten Bandung Barat (Studi Kasus Pada Badan Pengelolaan Keuangan Daerah Kabupaten Bandung Barat) - Anida Iqlima Pitriyani; Usmani (Indonesian Accounting Research Journal, 2020)
One component of the local tax in West Bandung Regency is the parking tax. In 2014-2018 parking tax receipts always increased and reached the target. However, in such an increase the parking tax is the type of local tax with the least revenuei compared to other taxes, whereas when viewed from potential, the parking tax has great potential. Thei purposei ofi thisi studyi isi toi findi outi thei factorsi thati affecti parking tax receipts in West Bandung Regencyi. The results of this study show there are factors that influence parking tax receipts including thei numberi ofi vehiclesi, thei numberi ofi WPi, thei availability ofi parkingi lots, parking rates, policies, and internal factors in the form of disagreements regarding the division of land between taxes and parking levies from BPKD and DISHUB